2022
DOI: 10.3390/diagnostics12040918
|View full text |Cite
|
Sign up to set email alerts
|

Role of AS-OCT in Managing Corneal Disorders

Abstract: Optical coherence tomography (OCT) is analogous to ultrasound biometry in the cross sectional imaging of ocular tissues. Development of current devices with deeper penetration and higher resolution has made it popular tool in clinics for visualization of anterior segment structures. In this review, the authors discussed the application of AS-OCT for diagnosis and management of various corneal and ocular surface disorders. Further, recent developments in the application of the device for pediatric corneal disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 97 publications
0
3
0
1
Order By: Relevance
“…Recently, epithelial thickness has been used as a diagnostic biomarker for different conditions [ 31 , 32 ]. For example, in DED and limbal stem deficiency patients, studies have shown thinning of the epithelial thickness compared to controls [ 33 ]. Epithelial thickness measured by the AS-OCT has the potential to be a biomarker in some ocular surface conditions even if it has a promising role in the diagnosis of keratoconus [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, epithelial thickness has been used as a diagnostic biomarker for different conditions [ 31 , 32 ]. For example, in DED and limbal stem deficiency patients, studies have shown thinning of the epithelial thickness compared to controls [ 33 ]. Epithelial thickness measured by the AS-OCT has the potential to be a biomarker in some ocular surface conditions even if it has a promising role in the diagnosis of keratoconus [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, AS-OCT can provide valuable information regarding the extent and location of subtle corneal changes, which can be difficult to ascertain at the slit-lamp. 10 For instance, in Thygeson's keratitis, AS-OCT is currently an important aid in differential diagnosis, demonstrating characteristic intra-epithelial lesions, guiding its proper management, which is distinct from initially identical diseases such as infectious keratitis. Our case suggests a similar value of the AS-OCT for ocular LP which is usually diagnosed once irreversible ocular surface disease have developed, presumably due to unrecognized progression of mild ocular surface signs.…”
Section: Discussionmentioning
confidence: 99%
“…It was repeated up to four times. Primary-graft failure (PGF) was defined as the failure of the pre-existing edema to resolve within 3 months of surgery, as measured with anterior segment-optical coherence tomography [ 27 ] at follow-up visits. Secondary-graft failure (SGF) was defined as the new emergence of corneal edema after 3 months.…”
Section: Methodsmentioning
confidence: 99%